2018
DOI: 10.1002/ccd.27526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sheath size and hemostasis time on radial artery patency after transradial coronary angiography and intervention in Japanese and non‐Japanese patients: A substudy from RAP and BEAT (Radial Artery Patency and Bleeding, Efficacy, Adverse evenT) randomized multicenter trial

Abstract: Background: During transradial (TR) access, it remains unclear whether differences in baseline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…To this regard, our finding that longer TR-band time was significantly associated with RAO is worth noting. In fact, this finding is in line with previous studies [ 31 , 32 , 33 , 34 ]. Interestingly, Lavi et al reported that shortening the haemostasis time to one hour is able to further reduce RAO incidence [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…To this regard, our finding that longer TR-band time was significantly associated with RAO is worth noting. In fact, this finding is in line with previous studies [ 31 , 32 , 33 , 34 ]. Interestingly, Lavi et al reported that shortening the haemostasis time to one hour is able to further reduce RAO incidence [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Procedure related parameters include recurring failed attempts of radial punctures, lack of aspirin pre-treatment, increased sheath-to-artery ratio and lack of periprocedural intravascular anticoagulation 10,[11][12][13] . Post-procedural risk factors specifically include non patenthemostasis 5,14,15 and prolonged time for hemostasis [16][17][18][19] . Anticoagulation during procedure is crucial to prevent RAO because thrombus formation is central factor leading to occlusion of radial artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the duration of compression needed, with practices ranging from as few as 60 min to as long as 6 hr as practiced in Japan. Longer compression time is associated with increased RAO occlusion rates and likely greater observation costs, while <60 min of compression has been associated with increased hematoma rates …”
Section: Radial Hemostasis Optionsmentioning
confidence: 99%